Narcolepsy and Orexins: An Example of Progress in Sleep Research - De La Herrán-Arita, Alberto K.; Guerra-Crespo, Magdalena; Drucker-Colin, René (Frontiers in Neurology, 2011)
Narcolepsy is a chronic neurodegenerative disease caused by a deficiency of orexin-producing neurons in the lateral hypothalamus (LH). It is clinically characterized by excessive daytime sleepiness and by intrusions into wakefulness of physiological aspects of rapid eye movement (REM) sleep such as cataplexy, sleep paralysis and hypnagogic hallucinations. The major pathophysiology of narcolepsy has been recently described on the bases of the discovery of the neuropeptides named orexins (hypocretins) in 1998; considerable evidence, summarized below, demonstrates that narcolepsy is the result of alterations in the genes involved in the pathology of the orexin ligand or its receptor. Deficient orexin transmission is sufficient to produce narcolepsy, as we describe here, animal models with dysregulated orexin signaling exhibit a narcolepsy-like phenotype. Remarkably, these narcoleptic models have different alterations of the orexinergic circuit, this diversity provide us with the means for making comparison, and have a better understanding of orexin cell physiology. It is of particular interest that the most remarkable findings regarding this sleep disorder were fortuitous and due to keen observations. Sleep is a highly intricate and regulated state, and narcolepsy is a disorder that still remains as one of the unsolved mysteries in science. Nevertheless, advances and development of technology in neuroscience will provide us with the necessary tools to unravel the narcolepsy puzzle in the near future. Through an evaluation of the scientific literature we traced an updated picture of narcolepsy and orexins in order to provide insight into the means by which neurobiological knowledge is constructed.